Lability classification of soil organic matter in the northern permafrost region - Peter Kuhry (Department of Physical Geography, Stockholm University); Jiří Bárta (Department of Ecosystem Biology, University of South Bohemia); Daan Blok (Department of Physical Geography and Ecosystem Science, Lund University); Bo Elberling (Center for Permafrost (CENPERM), Department of Geosciences and Natural Resource Management, University of Copenhagen); Samuel Faucherre (Center for Permafrost (CENPERM), Department of Geosciences and Natural Resource Management, University of Copenhagen); Gustaf Hugelius (Department of Physical Geography, Stockholm University); Christian J. Jørgensen (Center for Permafrost (CENPERM), Department of Geosciences and Natural Resource Management, University of Copenhagen); Andreas Richter (Centre for Microbiology and Environmental Systems Science, University of Vienna); Hana Šantrůčková (Department of Ecosystem Biology, University of South Bohemia); Niels Weiss (Department of Physical Geography, Stockholm University) (Biogeosciences, 2020)
The abstract is available here: https://uscholar.univie.ac.at/o:1301171 The abstract is available here: https://uscholar.univie.ac.at/o:1301171